Evolution of magnetic and bone mineral phases in heat‐treated bioactive glass containing zinc and iron oxides. (9th April 2016) - Shankhwar, Nisha; Singh, Rajendra Kumar; Srinivasan, Ananthakrishnan
Abstract : Melt‐quenched 15(ZnO, Fe2 O3 ) 50SiO2 ·20(CaO, P2 O5 ) 15Na2 O bioactive glass was heat treated at temperatures ( T A ) ranging from 550°C to 850°C for different time periods ( t A =1, 2 and 3 hours) to understand its devitrification characteristics. Crystallization of calcium sodium phosphate, zinc ferrite, magnetite, and hematite phases depended on heat treatment conditions. Decrease in saturation magnetizations ( M s ) with increase in t A of glass heat treated at T A ≥750°C is attributed to the formation of hematite which is a weak magnetic material. Magnetic properties as functions of T A and t A are interpreted on the basis of clustering of Fe ions, super‐exchange interaction between Fe 2+ and Fe 3+ ions and formation of ferrimagnetic and weakly magnetic iron oxide phases with different heat treatment conditions. Electron paramagnetic resonance parameters reveal the variations in site distortions and randomness in Fe ion environment in the matrix upon heat treatment. In vitro mineralization ability of the glass‐ceramics was evaluated by immersion in simulated body fluid (SBF) and monitoring both the pH variation of SBF and formation of hydroxyapatite surface layer as a function of immersion time. These studies help in assessing these glass‐ceramics for hyperthermia treatment and in optimizing the processing conditions for this application.